KONTEKSTUALISASI PROSES KEPERAWATAN DIABETES MELLITUS TIPE 2 BERBASIS NEEDS ANALYSIS - Tiarnida Nababan; Chrismis Novalinda Ginting (Jurnal Maternitas Kebidanan, 2022)
Although some previous studies have discussed the nursing process for type 2 diabetes mellitus; however, research that specifically discusses adapting the nursing process for type 2 diabetes mellitus through needs analysis has never been studied before. This systematic review aims to review some research publications on nurses' understanding of type 2 diabetes mellitus, the nursing process for patients with type 2 diabetes mellitus, and a needs analysis based type 2 nursing process training model. By using descriptive qualitative research methods, this study uses scientific journal publications in the last ten years as the object of research to describe the condition of nurses' understanding of type 2 diabetes mellitus, the nursing process of type 2 diabetes mellitus patients, and nursing training models based on needs analysis. The results of this systematic review revealed that most of the research journal articles focused on revealing the care of patients with diabetes mellitus by doctors, medical therapy for patients with diabetes mellitus, and comorbidities caused by diabetes mellitus. However, research on nursing training to intensify the implementation of the nursing process for patients with type 2 diabetes mellitus is still very rarely done. By observing this condition, research on the implementation of the nursing process for patients with type 2 diabetes mellitus based on analysis is very necessary to improve the quality of health services for patients with diabetes mellitus.